The Influence of Social Media on Millennial Political Participation: A Study of Bukittinggi - Syajad Al Furqan; Adlan Sanur (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
The use of social media as a means of information, especially in the political sphere, is expected to provide educational political information that can increase public political participation. On the one hand, social media provides great benefits as a space for communication and political participation, but on the other hand, it also presents various negative influences such as disinformation, pseudo-participation, and manipulation of public opinion. This study is a systematic review conducted through a literature search using Google and Google Scholar search engines with the keywords “political participation,” “social media,” and “the influence of social media on political participation.” The results of the study show that social media, especially among young voters or millennials, can increase the level of political participation quantitatively. Social media functions not only as a source of political information but also as a platform for participation and a tool for political communication. This condition is a strategic opportunity for political candidates to gain support, considering that most active social media users are millennials who are also first-time voters. This study discusses the use of social media by the younger generation in obtaining election information, including the features that are most frequently used. The findings show that millennial political participation tends to be superficial, such as following political issues, liking, sharing, and commenting.